El uso del programa picasa 3 como recurso didáctico para incentivar el aprendizaje sobre sistemas de dos ecuaciones lineales con 2 incógnitas en los estudiantes del décimo grado de educación básica de la unidad educativa fiscal José Ingenieros n° 1, de la ciudad de Loja, periodo 2013-2014 - Chamba Viñamagua, Ana Johana (2015)
The present Investigation had for object verify the importance of the application OF THE USE OF THE PROGRAM PICASA 3 AS DIDACTIC RESOURCE TO STIMULATE THE LEARNING ON SYSTEMS OF TWO LINEAR EQUATIONS WITH 2 MYSTERIES; it answered to a descriptive (diagnostic) design and pre experimentally; the phases that followed in his order were the following ones: Comprehensive, in that a mental map was elaborated, a plan of contents and there based theoretically every describer of the plan of contents on the system learning of equations; of diagnosis, where there was effected a diagnostic evaluation of the system learning of equations by means of criteria and indicators and taken again in surveys these criteria and indicators were applied to the students of the tenth year of EGB and to the teacher of mathematics; of modeling, in which it was defined, a procedural analysis of the functioning was realized and there designed plans of application of the efficiency of the use of the program PICASA 3 as didactic resource to strengthen the system learning of equations; of application, the same one that had delimited the program PICASA 3 as didactic resource, it facilitated to proceed to his application by means of workshops; and of valuation for, once applied the workshops, values the efficiency of the program PICASA 3 for the strengthening of the system learning of linear equations with 2 mysteries with the test I Seal Wilcoxon's Range. The principal findings in the present investigation were: difficulties, lacks or cognitive present needs in the system learning of two linear equations with 2 mysteries, can diminish or be mitigated with the application of the program PICASA3 as didactic resource by them.